Microstructural Alterations and Oligodendrocyte Dysmaturation in White Matter After Cardiopulmonary Bypass in a Juvenile Porcine Model. Issue 8 (August 2017) - Stinnett, Gary R.; Lin, Stephen; Korotcov, Alexandru V.; Korotcova, Ludmila; Morton, Paul D.; Ramachandra, Shruti D.; Pham, Angeline; Kumar, Sonali; Agematsu, Kota; Zurakowski, David; Wang, Paul C.; Jonas, Richard A.; et al.
Abstract : Background: Newly developed white matter (WM) injury is common after cardiopulmonary bypass (CPB) in severe/complex congenital heart disease. Fractional anisotropy (FA) allows measurement of macroscopic organization of WM pathology but has rarely been applied after CPB. The aims of our animal study were to define CPB‐induced FA alterations and to determine correlations between these changes and cellular events after congenital heart disease surgery. Methods and Results: Normal porcine WM development was first assessed between 3 and 7 weeks of age: 3‐week‐old piglets were randomly assigned to 1 of 3 CPB‐induced insults. FA was analyzed in 31 WM structures. WM oligodendrocytes, astrocytes, and microglia were assessed immunohistologically. Normal porcine WM development resembles human WM development in early infancy. We found region‐specific WM vulnerability to insults associated with CPB. FA changes after CPB were also insult dependent. Within various WM areas, WM within the frontal cortex was susceptible, suggesting that FA in the frontal cortex should be a biomarker for WM injury after CPB. FA increases occur parallel to cellular processes of WM maturation during normal development; however, they are altered following surgery. CPB‐induced oligodendrocyte dysmaturation, astrogliosis, and microglial expansion affect these changes. FA enabled capturing CPB‐induced cellular events 4 weeks postoperatively. Regions most resilient to CPB‐induced FA reduction were those that maintained mature oligodendrocytes. Conclusions: Reducing alterations of oligodendrocyte development in the frontal cortex can be both a metric and a goal to improve neurodevelopmental impairment in the congenital heart disease population. Studies using this model can provide important data needed to better interpret human imaging studies.